Enhancing meniscal repair with tough adhesive puncture sealing (TAPS) suture: A proof‐of‐concept study on bovine cadaveric knees - Stephanie Lamer; David Mazy; Marie‐Lyne Nault (Journal of Experimental Orthopaedics)
Abstract Purpose The objective was to use cyclic tensile loading to compare the gap formation at suture site of three different suture materials to repair bovine radial meniscal tears: (1) polyglactin sutures, (2) tough adhesive puncture sealing (TAPS) sutures and (3) ultra‐high molecular weight polyethylene (UHMWPE) sutures. Methods Twelve ex vivo bovine knees were dissected to retrieve the menisci. Complete radial tears were performed on 24 menisci, which were then separated into three groups and repaired using either pristine 2–0 polyglactin sutures, TAPS sutures (2–0 polyglactin sutures coated with adhesive chitosan/alginate hydrogels) or 2‐0 UHMWPE sutures with a single stitch. The repaired menisci were clamped onto an Instron machine and underwent cyclic loading between 5 and 25 N at a frequency of 0.16 Hz. Gap formation between the edges of the tear was measured after 500 cycles using an electronic caliper, when the meniscus was still on the Instron without any load applied. Results Mean gap formation was 5.22 mm (±1.70) for the 2–0 polyglactin sutures, 2.48 mm (±0.25) for the TAPS sutures, and 4.85 mm (±1.55) for the 2–0 UHMWPE sutures. The gap was significantly smaller in the TAPS sutures group compared to the two others because of better force dispersion, decreasing tissue damage by suture indentation and potentially leading to better meniscal healing. Conclusions From a biomechanical standpoint, coated sutures held the edges of radial meniscal tears closer together compared to conventional sutures. This technology has the potential to reduce tissue damage and improve the success rate of meniscal repairs. Level of Evidence controlled laboratory study.